Risk factors associated with an outbreak of equine coronavirus at a large farm in North Carolina - Hepworth-Warren, Kate L.; Erwin, Sara J.; Moore, Caroline B.; Talbot, James R.; Young, Kimberly A. S.; Neault, Michael J.; Haugland, Jennifer C.; Robertson, James B.; Blikslager, Anthony T. (Frontiers in Veterinary Science, 2023)
Background- Equine coronavirus (ECoV) leads to outbreaks with variable morbidity and mortality. Few previous reports of risk factors for infection are available in the literature. Objectives- To describe unique clinical findings and risk factors for infection and development of clinical disease. Animals- 135 horses on a farm affected by ECoV outbreak. Methods- Retrospective cohort study. Data obtained included age, breed, gender, activity level, housing, and feed at the onset of the outbreak. Factors were evaluated for assessment of risk of infection using simple logistic regression or Fisher’s exact test. Significance was set at p ≤ 0.05. Results/Findings- Forty-three of 54 (79.6%) horses tested on the farm were positive on fecal PCR for ECoV, and 17 horses (12.6%) developed clinical signs consistent with ECoV. Out of 17 horses in which the presence or absence of signs of colic was noted, 6 of 17 (35.3%) showed signs of colic. Three of these horses had small colon impactions, 2 of which required surgical intervention. Significant risk factors for having positive PCR results included being primarily stalled (OR 167.1, 95% CI 26.4-1719), housing next to a positive horse (OR 7.5, 95% CI 3.1-19.0), being in work (OR 26.9, 95% CI 4.6-281.9), being fed rationed hay vs ad libitum (OR 1558, 95% CI 130.8 to 15593), and being fed alfalfa hay (OR 1558, 95% CI 130.8 to 15593). Conclusions and Clinical Importance- This report describes risk factors for ECoV infection many of which were associated with intensive management of show horses. Clinicians should be aware that clinical signs vary and can include severe colic.